Time-Resolved Extracellular Matrix Atlas of the Developing Human Skin Dermis - Li, Mansheng; Li, Xiao; Liu, Binghui; Lv, Luye; Wang, Wenjuan; Gao, Dunqin; Zhang, Qiyu; Jiang, Junyi; Chai, Mi; Yun, Zhimin; Tan, Yingxia; Gong, Feng; et al. (Frontiers in Cell and Developmental Biology, 2021)
Skin aging is a physiological issue that is still relatively poorly understood. Studies have demonstrated that the dermal extracellular matrix (ECM) plays important roles in skin aging. However, the roles of the changes in ECM characteristics and the molecules that are secreted to the extracellular space and are involved in the formation of the dermal matrix from birth to old age remain unclear. To explore the way in which the ECM microenvironment supports the functions of skin development across different age groups is also poorly understood, we used a decellularization method and matrisome analysis to compare the composition, expression, and function of the dermal ECM in toddler, teenager, adult, and elderly skin. We found that the collagens, glycoproteins, proteoglycans, and regulatory factors that support skin development and interact with these core ECM proteins were differentially expressed at different ages. ECM expression markers occurring during the process of skin development were identified. In addition, our results elucidated the characteristics of ECM synthesis, response to skin development, and the features of the ECM that support epidermal stem cell growth via the basement membrane during skin aging.